Analisis Rasio Keuangan Dalam Menilai Kinerja Keuangan Pada Industri Kosmetik Terdaftar BEI Periode 2022 - Noviadry Nur Tamtama; Rahmawati Riantisari (eCo-Buss, 2023)
The development of the beauty industry increases every year. Even during the Covid-19 pandemic, this industry remained stable in facing the crisis. This condition certainly makes many investors look to invest their capital in this industry. The beauty industry listed on the Indonesian Stock Exchange (BEI) is PT. Mustika Ratu Tbk, PT. Martina Berto Tbk and PT. Unilever Indonesia Tbk. In order to help investors assess company performance, it is necessary to carry out financial ratio analysis. Financial ratio analysis in this study is liquidity analysis, asset management analysis, debt management analysis, profitability analysis and market value analysis. This study is qualitative in nature with data analysis using financial ratio analysis. The results of this study provide the conclusion that if the analysis of the cosmetics industry in 2022 uses industry averages according to Brigham Houston, there are several components that are above standard, such as profit margin and ROA owned by PT. Mustika Ratu Tbk and PT. Unilever Indonesia Tbk above standard. PT fixed asset turnover. Muatika Ratu Tbk which is above standard. If analyzed through comparisons between companies that are still in the same industry, the company PT. Unilever Indonesia Tbk has performed quite well in generating company profitability. Proven by the fairly large profit margin and ROA ratio. Keywords: Liquidity, Asset management, Debt management, Profitability, Market value